ANALISIS PERMINTAAN RUMAH TANGGA TERHADAP BERAS PRODUKSI KABUPATEN KUBU RAYA - Adi Suyatno, Ike Deviana, Novira Kusrini, (Jurnal Social Economic of Agriculture, 2014)
The purpose of this thesis is " To know the factors - factors that berpengaruhi in household demand on rice production Kubu Raya district and to determine the elasticity of demand for domestic rice production Kubu Raya District " . The method used in this study uses survey research locations selected by purposive sampling ( intentionally ) and respondents were selected directly at the study site ( accidental ) that is at the center of local sales of processed rice farmers Kubu Raya district ( Store Langsat Mas ) . Criteria for respondents who selected that consumer households who are married and are buying local rice ( rice produced by farmers in Kubu Raya district ) of sample was 40 respondents .. The variables examined in the study are the following : 1 ) Number of Family Members , 2 ) Local Rice Price , 3 ) . Non- local rice prices . , 4 ) . Household income . The results showed household demand functions to rice production Kubu Raya District as follows : Ln Y = -2.621 + 0.127 +1.536 ln JTK lnPdp - 0.163 + 0.358 lnHbl lnHbn + e. Domestic demand on rice production Kubu Raya regency significantly influenced by the number of family members while the local rice price factors , the price of rice non-local factors and factors of household income had no significant effect . Price elasticity at the request of the households of Kubu Raya regency rice production is inelastic , income elasticity suggests that local rice is included in the category of normal goods and that the cross-price analysis based on non- local rice is included as substitutes. Keywords : Demand , Local Rice , Kubu Raya , Elasticity .